Menggapai Ridho Allah Swt Dengan Menghindari Kikir (Isi Kandungan QS. Al-Lail [92]: 8-11) - Siti Nurjannah Gultom; Wirda Aini Rambe (Pusat Riset dan Inovasi Nasional, 2023)
Al-Quran is the word of Allah SWT in the form of miracles revealed by Him to humans. Through Gabriel with the intermediary of the last Messenger, Muhammad has the main function as a guide for humans as psychophysical beings who are worth worship. Among the features of the Al-Quran is that it is a book that is explained and easy to memorize. The Al-Quran is the main source in Islam and is a life guide for every Muslim, the Al-Quran does not only contain instructions about the relationship between humans and Allah, but also humans and humans. Like miserly, the Koran presents about miserly, miserly should not exist, because it damages human relations. This study aims to find the meaning of miserliness, by avoiding it in order to reach Allah's blessing. In the Indonesian dictionary, the word bakhil is miserly, lokek, and stingy. One of the liver disease is miserly. Miserliness ( miserly ) is a disease of the heart and a despicable mental attitude . Stingy is also stingy in using his wealth, even stinginess can be towards himself, especially towards other people. This miserly disease often afflicts people who strive in the way of Allah and is the cause of the suffering of Muslims today and this trait is a disease that must be cured. It is one of the bad and reprehensible qualities in all religious views. Miserliness and greed accompanied by a tendency to hoard as much wealth as possible can violate the values ​​of community life, cultured human life. In the Al-Quran there are messages and suggestions to pay attention to one another and be concerned for others, especially for those who are less fortunate. Stinginess and reluctance to share with others, especially those in need have a negative impact. Neither to oneself nor to others, so that there are many verses in the Koran that instruct sharing and charity, as well as the prohibition of being stingy. These various realities show that miser or miserly is an interesting issue to discuss because, firstly, its existence is quite complex and difficult to overcome. Second, there is a paradox, where on the one hand the social escalation of regiusitas is increasing, but on the other hand miser is still attached.